Frequency content of carrier oscillations along B-DNA polymers - Lambropoulos, K.; Mantela, M.; Simserides, C. (Progress in Electromagnetics Research Symposium, 2017)
We study the frequency content of an extra carrier oscillation along characteristic periodic B-DNA polymers made of N monomers. We employ two variants of the Tight-Binding approach, a wire model and an extended ladder model including diagonal hoppings. In the former, the site is a monomer, i.e., a base pair, while, in the latter, the site is a base. Initially, we focus on the Fourier Spectra of the probabilities to find the extra carrier at each monomer, having placed it at time zero at a specific monomer. Using the Fourier amplitude of each component of the frequency spectrum, we define the weighted mean frequency (WMF) for each site, a measure of its frequency content. To obtain a measure of the overall frequency content of carrier oscillations in the polymer, we define the total weighted mean frequency (TWMF), averaging the WMFs of all sites weighting over the probabilities of finding the extra carrier at each site. The frequency content is generally in the THz domain. Finally, we also give an example of an aperiodic sequence, the (A, T) Cantor dust.